ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMK NEGERI 1 PRABUMULIH PADA MATERI BARISAN ARITMETIKA - Sistyawati, Risda Intan; Anggraini, Suci; Andinasari, Andinasari (Universitas Batanghari Jambi, 2024)
This research aims to describe the results of the analysis of the mathematical communication skills of class This research method is descriptive qualitative research. The subjects of this research were class X AKL 1 students consisting of 30 students consisting of 28 female students and 2 male students. The instrument in this research was to use a test instrument for mathematical communication skills in the form of 3 questions. The results of this research indicate that students' ability to complete mathematical communication skills is still lacking or low. This can be seen from the results of the recapitulation of the overall answers of students who answered correctly as much as 34.4%, answered incorrectly as much as 41.11%, and did not answer as much as 24.4%. Apart from that, it can be seen from the results of the student score conversion that students' mathematical communication skills are in the very low category, namely students who get a score of less than 61%.